NOTE ON COMPLEMENT GRAPHS - REDDY*, P. SREENIVASULU; EJERSA, MELAKU ABERA (International Journal of Mathematical Archive, 2018)
In this article we generalize the complement for all types of graphs and we proved some primary results on complement of graphs.